Fear of Labor Rigidities: The Role of Expectations on Employment Growth in Peru - Pablo Lavado; Gustavo Yamada (Institute for the Study of Labor (IZA), 2015)
Many studies have been conducted to analyze the effect of stricter Employment Protection Legislation (EPL). However, almost all of them has focused on an ex-post impact; leaving aside a second but equally important channel: expectations. This paper aims to analyze the role of expectations on Peruvian formal and informal labor market; using news as our identification variable. We use the monthly number of news related to the approval of the General Labor Law (GLL), a proposal entailing future stronger labor rigidities, from January 2001 to May 2012. Using the Permanent Employment Survey (EPE), we find a negative relation between expectations towards a stricter labor market and both employment and average income. News mainly affect formal occupied EAP, arousing a substitution effect from formal to informal employment. We also discover that the effect of expectations differs in periods with higher versus lower GDP growth. Finally, we find some evidence supporting news having a cumulative effect: the larger the previous stock of news, the weaker the effect.
Keywords: J21; J23; J24; J46; J32; 330; employment protection legislation; expectations; labor law; informal labor market